The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1462-2920.12454
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of Verrucomicrobia methanotrophs in geothermal and acidic environments

Abstract: Recently, methanotrophic members of the phylum Verrucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16S rRNA gene amplicons. Putative methanotrophic Verrucomicrobia were found in samples covering a broad temperature range (22.5-81.6°C), but only in acidic conditions (pH 1.8-5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
119
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 48 publications
3
119
0
Order By: Relevance
“…The latter were only recently discovered and appear to be restricted to acidic geothermal environments (Sharp et al, 2014). By contrast, methanotrophic proteobacteria occur in a wide range of habitats where both methane and oxygen are available (Nazaries et al, 2013) and affiliate with the classes Gammaproteobacteria (type I methanotrophs) and Alphaproteobacteria (type II methanotrophs).…”
Section: Introductionmentioning
confidence: 99%
“…The latter were only recently discovered and appear to be restricted to acidic geothermal environments (Sharp et al, 2014). By contrast, methanotrophic proteobacteria occur in a wide range of habitats where both methane and oxygen are available (Nazaries et al, 2013) and affiliate with the classes Gammaproteobacteria (type I methanotrophs) and Alphaproteobacteria (type II methanotrophs).…”
Section: Introductionmentioning
confidence: 99%
“…The three thermophilic strains belonging to the genus Methylacidiphilum share low pH optima (2 to 3.5) and high temperature optima (55 to 60°C) (7). In addition, 16S rRNA gene sequences from different geothermal sites showed identities of only 95% to 99% to the 16S rRNA gene sequence of M. fumariolicum SolV (8,14,16). This indicated that a larger diversity in verrucomicrobial methanotrophs might exist in geothermal environments.…”
mentioning
confidence: 97%
“…Like most other aerobic methane oxidizers, the Verrucomicrobia use particulate methane monooxygenase (pMMO) to catalyze the first step of the methane oxidation. Unlike most proteobacterial methanotrophs (7), but like Methylomirabilis oxyfera (belonging to the NC10 phylum) (12), M. fumariolicum SolV (13) and M. infernorum V4 (14) grow as autotrophs, using only carbon dioxide as the carbon source via the Calvin cycle.All verrucomicrobial methanotrophs known to date have been enriched from geothermal environments (7,15,16), and 16S rRNA gene surveys indicated their presence to be mainly limited to such environments (16). The three thermophilic strains belonging to the genus Methylacidiphilum share low pH optima (2 to 3.5) and high temperature optima (55 to 60°C) (7).…”
mentioning
confidence: 99%
“…However, more recently, a number of type II methanotrophs (Methylocella, Methylocapsa, and Methylocystis) have been characterized as facultative methanotrophs capable of conserving energy for growth on multicarbon compounds such as acetate, pyruvate, succinate, malate, and ethanol (12). Although members of the phylum Verrucomicrobia have been widely detected in peatlands, none has been definitively linked to methanotrophy, and thus more research is needed to ascertain the role of Verrucomicrobia in the carbon cycle of peatlands (8,13,14,15,16).Aerobic methane oxidation in proteobacterial methanotrophs is catalyzed by the enzyme methane monooxygenase (MMO), either particulate MMO (pMMO) or a soluble MMO (sMMO). The genes pmoA (encoding the 27-kDa subunit of pMMO) and mmoX (encoding the alpha-subunit of the hydroxylase of sMMO) as well as 16S rRNA genes have been used most often as molecular markers to characterize methanotrophs in peatlands and other environments (6,17,18,19,20,21,22,23).…”
mentioning
confidence: 99%
“…However, more recently, a number of type II methanotrophs (Methylocella, Methylocapsa, and Methylocystis) have been characterized as facultative methanotrophs capable of conserving energy for growth on multicarbon compounds such as acetate, pyruvate, succinate, malate, and ethanol (12). Although members of the phylum Verrucomicrobia have been widely detected in peatlands, none has been definitively linked to methanotrophy, and thus more research is needed to ascertain the role of Verrucomicrobia in the carbon cycle of peatlands (8,13,14,15,16).…”
mentioning
confidence: 99%